The Development of Quantitative Instruments to Evaluate Cognition and Competency of Forensic Nursing Science. Issue 6 (November 2016) - Drake, Stacy A.; Langford, Rae; Young, Anne
Abstract : Abstract: Few instruments are available to evaluate fundamental forensic nursing science practice. A cognitive exam to assess knowledge and a practical competency rubric to assess skill proficiency were developed and examined for validity and reliability. Content validity of the cognitive exam was investigated using a test blueprint as well as a panel of experts in forensic science and test construction. The same panel inspected the competency rubric. Pilot testing of both instruments was then conducted to assess reliability. Internal consistency of the cognitive exam was low, leading to revision and retesting; interrater reliability of the competency rubric was acceptable.